eCM 2013
DOI: 10.22203/ecm.v026a16
|View full text |Cite
|
Sign up to set email alerts
|

Generation of co-culture spheroids as vascularisation units for bone tissue engineering

Abstract: Cell spheroids represent attractive building units for bone tissue engineering, because they provide a threedimensional environment with intensive direct cellcell contacts. Moreover, they allow for co-culture of both osteoblasts and vessel-forming cells, which may markedly increase their survival and vascularisation after transplantation. To test this hypothesis, we generated coculture spheroids by aggregating different combinations of primary human osteoblasts (HOB), human dermal microvascular endothelial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 30 publications
2
54
0
2
Order By: Relevance
“…Various scaffolds coated with ECs and OBs showed the expression of angiogenic genes, and the formation of vessel‐like structures in vitro . 52 In vivo studies demonstrated that co‐culture systems promoted the formation of vascularized bone tissue, and the vessel‐like network in scaffolds anastomosed well with the host vasculature . In addition, many research groups have studied the co‐culture system of ECs and MSCs.…”
Section: Terminally Differentiated Vascular Cellsmentioning
confidence: 99%
“…Various scaffolds coated with ECs and OBs showed the expression of angiogenic genes, and the formation of vessel‐like structures in vitro . 52 In vivo studies demonstrated that co‐culture systems promoted the formation of vascularized bone tissue, and the vessel‐like network in scaffolds anastomosed well with the host vasculature . In addition, many research groups have studied the co‐culture system of ECs and MSCs.…”
Section: Terminally Differentiated Vascular Cellsmentioning
confidence: 99%
“…Multicellular spheroids are cultivated as 3D-cell culture models employed in cancer research [37][38][39] and pharmaceutical screening [40,41]; in addition, applications of spheroids as building blocks in tissue engineering have been envisaged [36,[42][43][44]. Thus, rendering multicellular spheroids with magnetic functionality is deemed important for assembly of artificial tissues, and magnetic nanoparticles have been introduced into cells prior to fabrication of spheroids [9].…”
Section: Fabrication Of Layered Planar Tissue Constructs and Multicelmentioning
confidence: 99%
“…The results of the present study demonstrated that cell spheroids formed from a single or two cell types preserved viability and may have promoted proliferation in the three-dimensional environment. Previous reports have indicated that co-culture spheroids generated by aggregating different combinations of primary human osteoblasts and human dermal microvascular endothelial cells exhibit excellent properties of preserving viability and promoting proliferation and vascularization (26). It may be suggested that the co-culture technique may be used to generate functional units for tissue-engineering purposes.…”
Section: Discussionmentioning
confidence: 99%